Analisis Strategi Bauran Pemasaran (Marketing Mix) dalam Perspektif Ekonomi Islam: Studi Kasus pada UMKM Ma’Rika di Kecamatan Cikupa - Fathurrohman, Muhammad Khaeru (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
This study aims to analyze the marketing mix strategy consisting of 4 components or 4P, namely product, price, place, and promotion at Ma'Rika MSMEs in Dukuh Village, Cikupa District, Tangerang Regency, Banten Province from an Islamic economic perspective. This form of research employs qualitative methods with a descriptive approach. The data collection method uses observation, interviews with business owners and production employees totaling 5 people, and documentation. Data reduction, data presentation, and conclusions or verification are part of the data analysis techniques in this study. The results showed that Ma'Rika MSMEs in Cikupa District have implemented a marketing mix strategy in an Islamic economic perspective both in terms of products that prioritize halal and good principles (halalan thayyiban), prices that are affordable and free from elements of injustice and price discrimination, strategic business places and have carried out samsarah activities, and promotional activities prioritizing morals and honesty values.